Maps, vibration or gaze? Comparison of novel navigation assistance in indoor and outdoor environments. (2nd January 2017) - Gkonos, Charalampos; Giannopoulos, Ioannis; Raubal, Martin
Abstract: Pedestrian navigation assistance is often utilized in familiar as well as in unfamiliar environments. In recent years, several novel approaches have been introduced relying on map-based, vibrotactile or gaze-based interaction. We introduce a novel interaction concept named 'VibroGaze' that combines the benefits of vibrotactile and gaze-based interaction for pedestrian navigation. Furthermore, we present the results of a between subjects experiment with 40 participants for the evaluation of four of the most novel pedestrian navigation approaches in an indoor (multi-level building) as well as an outdoor setting. The results showed that our proposed navigation concept can effectively assist the users during navigation. Moreover, the findings revealed differences between the two tested environments and suggest that the typical map-based approach is still the most efficient navigation aid for indoor environments.